2003
DOI: 10.1067/msy.2003.169
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of errors reported by surgeons at three teaching hospitals

Abstract: Subjective incident reports gathered through interviews allow identification of characteristics of surgical errors and their leading contributing factors, which may help target research and interventions to reduce such errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
537
4
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 922 publications
(582 citation statements)
references
References 50 publications
(42 reference statements)
14
537
4
15
Order By: Relevance
“…Indirect effects on cost may result from the fact that trainees commit significantly more errors due to lack of technical competence or knowledge than do their non-trainee counterparts, and trainee errors are more complex than non-trainee errors (Singh et al 2007). Gawande et al (2003) reported that the most commonly cited system factor contributing to errors at the three teaching hospitals studied was inexperience or lack of competence in a surgical task.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect effects on cost may result from the fact that trainees commit significantly more errors due to lack of technical competence or knowledge than do their non-trainee counterparts, and trainee errors are more complex than non-trainee errors (Singh et al 2007). Gawande et al (2003) reported that the most commonly cited system factor contributing to errors at the three teaching hospitals studied was inexperience or lack of competence in a surgical task.…”
Section: Discussionmentioning
confidence: 99%
“…This plot shows the score constantly underpredicted major complications and as such is insufficiently accurate to serve as a comprehensive risk stratification tool. 3 of surgical adverse events occur [9,10,20]. Patients with low scores should be recognized to be at an elevated risk for major complications, even patients whose baseline characteristics would suggest they otherwise are at low risk.…”
Section: Discussionmentioning
confidence: 99%
“…Communication and teamwork failures are often cited as the most common cause of adverse events [1][2][3][4][5] . The Joint Commission identified communication as a critical factor in more than 65% of reported sentinel events 6 .…”
Section: Introductionmentioning
confidence: 99%